2023
DOI: 10.1007/s00125-022-05854-8
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in cancer mortality trends in people with type 2 diabetes: 20 year population-based study in England

Suping Ling,
Francesco Zaccardi,
Eyad Issa
et al.

Abstract: Aims/hypothesis The aim of this study was to describe the long-term trends in cancer mortality rates in people with type 2 diabetes based on subgroups defined by sociodemographic characteristics and risk factors. Methods We defined a cohort of individuals aged ≥35 years who had newly diagnosed type 2 diabetes in the Clinical Practice Research Datalink between 1 January 1998 and 30 November 2018. We assessed trends in all-cause, all-cancer and cancer-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…The importance of comorbidities enhancing risk of death is supported by the finding that Charlson index was an important predictor of mortality and survival. The observation that cancer was one of the major causes of death associated with SH in T2D is consistent with the increasing incidence of malignancy observed in older people (above age 65 years) with T2D in England 35 . The present study was too small to identify every disease state associated with SH, other than cancer and cardiorenal disease, although several relevant medical conditions have been identified 3,36,37 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The importance of comorbidities enhancing risk of death is supported by the finding that Charlson index was an important predictor of mortality and survival. The observation that cancer was one of the major causes of death associated with SH in T2D is consistent with the increasing incidence of malignancy observed in older people (above age 65 years) with T2D in England 35 . The present study was too small to identify every disease state associated with SH, other than cancer and cardiorenal disease, although several relevant medical conditions have been identified 3,36,37 .…”
Section: Discussionsupporting
confidence: 79%
“…The observation that cancer was one of the major causes of death associated with SH in T2D is consistent with the increasing incidence of malignancy observed in older people (above age 65 years) with T2D in England. 35 The present study was too small to identify every disease state associated with SH, other than cancer and cardiorenal disease, although several relevant medical conditions have been identified. 3,36,37 The non-DM individuals represent a group with serious ill health associated with life-threatening medical conditions.…”
Section: Discussionmentioning
confidence: 91%
“…6 During their disease, patients with lower SES also more often face complications and a reduced life expectancy compared with their counterparts with a higher SES. 7,8 Focusing on type 1 diabetes, SES influences glycaemic control in both children and adults. 9,10 Use of diabetes technology, such as continuous subcutaneous insulin infusion (CSII) and continuous glucose monitoring (CGM), is, apart from reimbursement policies, also influenced by SES-related factors at all ages.…”
Section: Introductionmentioning
confidence: 99%
“…In this patient group, SES inequity commences before the first stages of the disease, as SES is known to influence the prevalence of diabetes 6 . During their disease, patients with lower SES also more often face complications and a reduced life expectancy compared with their counterparts with a higher SES 7,8 . Focusing on type 1 diabetes, SES influences glycaemic control in both children and adults 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological studies have reported a transition from cardiovascular diseases to cancer as the leading cause of excess death associated with diabetes mellitus (DM) ( 1 , 2 ). Cancer mortality among people with DM, especially type 2 (T2) DM, is approximately 30%-50% higher than in the general population, particularly for pancreatic, liver, colorectal, and endometrial cancers ( 3 , 4 ). Clinical and preventive efforts must be directed at fighting DM-related risk factors for cancer to reduce the excess mortality risk in individuals with DM.…”
Section: Introductionmentioning
confidence: 99%